TINJAUAN YURIDIS PEMBAGIAN HARTA GONO-GINI AKIBAT PERCERAIAN DALAM PERSPEKTIF HUKUM PERDATA (Studi Analisa Putusan Nomor 282 K/Pdt/2014) - Aurilya, Tasya; Hartono, Rudy (UNES Law Review, 2022)
This study aims to find out the distribution of gono-gini assets can be rejected by the judge on divorce decisions, to know that a lawyer in a divorce lawsuit can also be sued, and about the considerations of the panel of judges in deciding the case for the distribution of gono-gini assets due to divorce for the husband. To achieve this goal, this research uses a juridical-normative approach which is carried out based on a review of library materials or secondary data. The type of this research is descriptive analysis, with the type of data consisting of 2 (two), namely primary data and secondary data. While the data analysis technique used in this research is qualitative data analysis technique. The results of the study show that the agreement in marriage regarding the assets of Gono Gini and child custody and other matters obtained in marriage, the author takes the example of a divorce case and the distribution of property which has reached the level of cassation, this agreement is strong evidence especially made before a Notary so that post-divorce is not so difficult to prove about the distribution of property Gono Gini. It should be remembered that the divorce decision does not automatically decide or determine the distribution of marital property in marriage. The application for the distribution of gonorrhea assets can be submitted after the divorce decision has permanent legal force. For a married couple whose marriage is registered with the civil registry office, the lawsuit is submitted to the District Court where the Defendant lives. Divorce is something that often happens in the modern era. After living together for a long time, many couples decide to divorce because of incompatibility in married life. Plus the various problems and pressures that come from here and there. During the divorce process, one thing that cannot be overlooked is the assets of Gono Gini. The division of property is also a very crucial moment and is often debated by the divorced parties.